Development of a new route for cation exchange membrane fabrication by using GO reinforced styrenated oil - ALEMDAR YAYLA, NESLİHAN (My University, 2022)
© 2022 Elsevier B.V.A novel route was developed for cation exchange membrane (CEM) fabrication by using GO reinforced styrenated oil polymeric structure and the impact of polymer type (PS/PS-oil), graphene oxide amount (0.5,1,3, and 5 wt%), and sulfonation time (6,12, and 24 h) on the characteristics of prepared membranes (contact angle, water uptake, ion exchange capacity, DS(%), electron conductivity) were investigated for the first time in the current study. The results showed that higher values of water absorption, ion exchange capacity, and electron conductivity were obtained for GO-PS-oil-based membranes compared to GO-only PS based membranes under all experimental conditions. Also, it was seen that ion-exchange capacity and water uptake capacity were directly related to the GO amount and sulfonation time of the polymer. The maximum value obtained for ion exchange capacity was 7.7 meq/g for 5%GO incorporated-PS-oil based membrane sulfonating for 24 h. The obtained IEC values for all experimental conditions in this study are relatively high compared to other PS based membranes studied in the literature. The membrane\"s electrochemical characteristics (conductivity, flux and permeability) were also determined in an electrodialysis test cell. All obtained results indicated that CEM fabricated by this new approach could be utilized for electrodialysis applications in the future.
Keywords: Kimya Mühendisliği ve Teknolojisi; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, ÇEVRE; MÜHENDİSLİK, KİMYASAL; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; ENGINEERING, ENVIRONMENTAL; ENGINEERING, CHEMICAL; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Genel Kimya; Fizik Bilimleri; Çevre Kimyası; Biyokimya; Genel Kimya Mühendisliği; Polimerler ve Plastikler; Malzeme Kimyası; General Chemistry; Physical Sciences; Environmental Chemistry; Biochemistry; General Chemical Engineering; Polymers and Plastics; Materials Chemistry; Cation exchange membrane; Graphene oxide; Polystyrene; Styrenated oil